Strengthening of ceramics treatments, tests, and design applications - Kirchner, Henry P. (Manufacturing engineering and materials processing, 1979)
Strengthening of Ceramics: Treatments: Tests, and Design Applications describes and evaluates the processes and analyzes their results in terms of strength, resistance to thermal shock and impact damage, and subcritical crack growth. The book also presents valuable information regarding potential applications of the treatments and their limitations, design considerations, and costs.